The complexity turn in human resources theory and research - Hsiao, J.; Jaw, C.; Huan, T.; Woodside, Arch (2017)
This study proposes and tests empirically a configural asymmetric theory of the antecedents to hospitality employee happiness-at-work and managers' assessments of employees' quality of work-performance. The study confirms and goes beyond prior statistical findings of small-to-medium effect sizes of happinessperformance relationships. The study merges data from surveys of employees (n = 247) and surveys completed by their managers (n = 43) and by using qualitative comparative analysis via the software program, fsQCA.com. The study analyzes data from Janfusan Fancyworld, the largest (in revenues and number of employees) tourism business group in Taiwan; Janfusan Fancyworld includes tourist hotels, amusement parks, restaurants and additional firms in related service sectors. The findings support the four principles of configural analysis and theory construction: recognize equifinality of different solutions for the same outcome; test for asymmetric solutions; test for causal asymmetric outcomes for very high versus very low happiness and work performance; and embrace complexity. Additional research in other firms and additional countries is necessary to confirm the usefulness of examining algorithms for predicting very high (low) happiness and very high (low) quality of work performance. The implications are substantial that configural theory and research will resolve perplexing happiness-performance conundrums. The study provides algorithms involving employees' demographic characteristics and their assessments of work facet-specifics which are useful for explaining very high happiness-at-work and high quality-of-work performance (as assessed by managers)-as well as algorithms explaining very low happiness and very low quality-of-work performance. The study is the first to propose and test the principles of configural theory in the contest of hospitality frontline service employees' happiness-at-work and managers' assessments of these employees quality of work performances.